C24‐Ceramide Drives Gallbladder Cancer Progression Through Directly Targeting Phosphatidylinositol 5‐Phosphate 4‐Kinase Type‐2 Gamma to Facilitate Mammalian Target of Rapamycin Signaling Activation. Issue 2 (26th November 2020) - Zhang, Yonglong; Wang, Hui; Chen, Tao; Wang, Haolu; Liang, Xiaowen; Zhang, Yuchen; Duan, Jinlin; Qian, Shenjiao; Qiao, Ke; Zhang, Lei; Liu, Yanfeng; Wang, Jian
Abstract : Background and Aims: The wide prevalence of chemoresistance and compromised early diagnosis of gallbladder cancer (GBC) has led to poor patient prognosis, requiring sustained efforts for the identification of effective biomarkers and therapeutic intervention. Ceramides have emerged as intracellular signaling molecules linked to tumorigenesis and therapeutic response in cancers. However, the clinical relevance of ceramides with GBC has not been investigated. Approach and Results: In the present study, we revealed aberrant gene expressions (e.g., serine palmitoyltransferase 1 [SPTLC1] and ceramide synthase 2 [CERS2]) of de novo ceramide biosynthesis and length‐specific ceramide production in GBC tissues. Analyses of serum ceramide pattern in healthy controls, gallbladder stone, and GBC patients identified C24‐Ceramide as a potential diagnostic biomarker for patients with GBC. Importantly, elevation of SPTLC1, CERS2, and its product, C24‐Ceramide, was associated with tumor staging, distal metastasis, and worse prognosis. In line with this, C24 ‐Ceramide promoted GBC cell proliferation and migration in vitro and in vivo . Mechanistically, C24‐Ceramide directly bound to phosphatidylinositol 5‐phosphate 4‐kinase type‐2 gamma (PIP4K2C), a regulator of mammalian target of rapamycin (mTOR), to facilitate mTOR complex formation and activation. C6‐Ceramide, an analogue of natural ceramide, competed with C24‐Ceramide for PIP4K2C binding, thereby abrogating C24‐Ceramide–mediated mTOR signaling activation and oncogenic activity. Furthermore, stimulation with C6‐Ceramide significantly suppressed the proliferative and metastatic capacity of GBC cells in vitro and in vivo, which was dependent on PIP4K2C. Conclusions: Our findings highlight the clinical relevance of ceramide metabolism with GBC progression and identify C24‐Ceramide as a diagnostic biomarker for GBC. We propose that PIP4K2C is indispensable for C6‐Ceramide as a potential therapeutic intervention for GBC through a direct competition with C24‐Ceramide.